The Education of Artists in Ancient Greece - Corso, Antonio (Hyperboreus, 2013)
In this article, the issues concerning the education of ancient artists from the early archaic period until the early Hellenistic times are addressed. The whole corpus of passages of ancient authors concerning this topic is cited and discussed as well as the inﬂuence of philosophical ideas and of the mentality of different periods upon the training and learning of artists. Thus the history of this subject from the 8th c. BC until the early 3rd c. BC is attempted as far as it is allowed by the available surviving evidence.